2012
DOI: 10.5664/jcsm.2266
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Race, and Excessive Daytime Sleepiness

Abstract: The results suggested the novel possibility that VitDd-related disease has a yet-to-be-identified mechanistic role in the presentation of sleepiness, sleep disorders, or both. Further research is needed to clarify the mechanism(s) involved in producing the complex relationships noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
66
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 27 publications
5
66
4
4
Order By: Relevance
“…It is clear that there is a link between lipids, such as polyunsaturated fatty acids, cholesterol or vitamin D and various neuropsychiatric diseases. For example, vitamin D deficiency can impact mental health in various ways: as relevant for depression, it can cause seasonal affective disorders (discomfort, depression, fatigue); is relevant to schizophrenia and autism, as the foetal brain develops vitamin D deficiency may cause permanent brain function impairment [119]; it leads to sleep disorders [120]. It is also hypothesised that vitamin D deficiency in adults may lead to parental germ cell degradation, causing autistic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that there is a link between lipids, such as polyunsaturated fatty acids, cholesterol or vitamin D and various neuropsychiatric diseases. For example, vitamin D deficiency can impact mental health in various ways: as relevant for depression, it can cause seasonal affective disorders (discomfort, depression, fatigue); is relevant to schizophrenia and autism, as the foetal brain develops vitamin D deficiency may cause permanent brain function impairment [119]; it leads to sleep disorders [120]. It is also hypothesised that vitamin D deficiency in adults may lead to parental germ cell degradation, causing autistic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…1 about our recent publication, 2 that a relationship between the Epworth Sleepiness Scale score (ESSs) and circulating 25-OH Vitamin D is interesting, but disagree that the research as presented was confusing. Instead, we would suggest a more accurate assessment is that the identifi ed relationships are complex and requiring of further study.…”
mentioning
confidence: 99%
“…T he new research by McCarty et al 1 titled "Vitamin D, Race, and Excessive Daytime Sleepiness" was very interesting as well as somewhat confusing. The authors reported that more than half of their patients with somatic pain and sleep disruption had vitamin D defi ciency.…”
mentioning
confidence: 99%